ANALISA TEGANGAN ELBOW SPIRAL INLET PADA BEJANA TEKAN SIKLON PEMISAH UAP DAN AIR GEOTHERMAL MENGGUNAKAN ANSYS - Asbar Razali (Jurnal Teknologi, 2014)
Separating tool like cyclone is also used as a separator between steam and water in geothermal, which most of its vital components dominated from water and steam, The voltage analysis is necessary as a reference of integrated material when operating and distributing mechanical load received by object structure.This research is aimed to observe the level of safety occurred in inlet spiral elbow by using ANYSYS. This research used SA-516 Gr. 70,SA 106 Gr.B, and SA 36 materials which are appropriate based on ASTM standard. The materials modeling used by using Solidworks 2013 software. The analyzing system used in this research is Static Structural by choosing the result of voltage analys solution using von-mises and Total Deformation. The result showed that in cyclone separator of pressure vessel with pressure given 1.386 MPa gained the maximum voltage,432,72 N/mm2 and the distribution of maximum deformation was 5.099 mm